Respuestas

2012-05-27T03:15:31+02:00

(5x-2y+z=24)*3= 15x-6y+3z= 72

   resto con:       x-4y+3z=26

                      > 14x-2y= 46...(1)

luego

            (2x+5y-2z=-14)*3= 6x+15y-6y=-42

sumo con:(x-4y+3z=26)*2=  2x-8y+6z =52

                                     >8x+7y= 10...(2)

de(1)y(2):

                 ( 14x-2y= 46)*7:98y-14y=322

                  (8x+7y= 10)*2: 16x+14y= 20

                                     >  124x= 332          
                                              x= 83/31 

resolviendo en los otros datos

y=  354/217  , z=2485/217